REVISITING A CULTURE OF TOLERANCE RELATING TO RELIGIOUS UNFAIR DISCRIMINATION IN SOUTH AFRICA (PART 1) - Radley Henrico (Obiter, 2017)
On account of its nature and scope, this article has been divided into two parts. The aim of this work is to explore religious unfair discrimination in South Africa in the context of the imperative of the need to tolerate differences. In Part 1, the importance of tolerance of differences in a secular multicultural society will be discussed. When the expression of religious freedom in the workplace or in greater society conflicts with other fundamental rights, the balancing of these conflicting rights is never a simple exercise. Whilst the adjudication of such conflicting rights may call for the imperatives of rationality, reasonableness, and proportionality to be applied, such conflict cannot only be conceived of in terms of the lens of adjudication. The need to live in a multicultural, secular society overflowing with divergent interests demands a culture of accommodation. This article further examines the fact that whether tolerance is conceived of as “thin” or “thick” tolerance, it is essentially concerned with a situation of forbearance and is not celebratory. In the spirit of commitment to true democratic transformation, it is argued that the need to celebrate differences is more imperative than merely tolerating differences.